2006
DOI: 10.1210/en.2005-1159
|View full text |Cite
|
Sign up to set email alerts
|

Large Effects from Small Exposures. III. Endocrine Mechanisms Mediating Effects of Bisphenol A at Levels of Human Exposure

Abstract: Over 6 billion pounds per year of the estrogenic monomer bisphenol A (BPA) are used to manufacture polycarbonate plastic products, in resins lining metal cans, in dental sealants, and in blends with other types of plastic products. The ester bond linking BPA molecules in polycarbonate and resins undergoes hydrolysis, resulting in the release of free BPA into food, beverages, and the environment, and numerous monitoring studies now show almost ubiquitous human exposure to biologically active levels of this chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
615
2
15

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 883 publications
(651 citation statements)
references
References 137 publications
19
615
2
15
Order By: Relevance
“…Furthermore, spine synapse proliferation seems not to require high concentrations of estradiol in normal females; endogenous stores are adequate. In fact, Tanapat et al (2005) found that low doses of estradiol enhanced proliferation while high doses did not; U-shaped or inverted U-shaped functions are a common finding in endocrinology (Welshons et al, 2006). Cooke and Wooley (2005), in their review of these relationships, also noted evidence that, during the period of elevated synaptogenesis, spatial navigation performance improved, followed by diminished performance when synaptogenesis waned.…”
Section: Estrogensmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, spine synapse proliferation seems not to require high concentrations of estradiol in normal females; endogenous stores are adequate. In fact, Tanapat et al (2005) found that low doses of estradiol enhanced proliferation while high doses did not; U-shaped or inverted U-shaped functions are a common finding in endocrinology (Welshons et al, 2006). Cooke and Wooley (2005), in their review of these relationships, also noted evidence that, during the period of elevated synaptogenesis, spatial navigation performance improved, followed by diminished performance when synaptogenesis waned.…”
Section: Estrogensmentioning
confidence: 99%
“…Bisphenol A, by conventional assays, would be considered a weak estrogen. Through enzyme induction, rather than by binding to the estrogen receptor, it enhances cell proliferation to produce estrogen-like results (Welshons et al, 2006). It is not an estrogen, that is, in the conventional sense, and, in fact, as shown by MacLusky et al (2005b), it can also counteract the effects of estrogens.…”
Section: Endocrine Disruptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…While excess energy intake and a sedentary lifestyle are known risk factors for gaining weight, there has been increasing interest in the effects that environmental chemicals may have on the development of obesity (4) . Food and water provide us with essential nutrients; however, food and water are also sources of exposure to environmental chemicals, including pesticides (5,6) , food packaging and processing-derived contaminants such as bisphenol A (BPA) and phthalates (7)(8)(9)(10)(11)(12)(13)(14)(15) , and naturally occurring contaminants such as arsenic (16,17) . Chemicals detected in the food and water supply include endocrine-disrupting chemicals, a class of chemicals that interfere in some way with the normal functioning of the endocrine system and includes chemicals that may alter hormonal regulation of body weight.…”
mentioning
confidence: 99%
“…A recent study by Calafat et al [38] found that up to 95% of their demographically diverse sample of the United States adult population had detectable BPA in their urine, with concentrations reported to range in the nanomolar range (mean concentration in urine of 1.33 lg/l). Additionally, several other studies have reported adult BPA levels in the nanomolar range (using both serum and urine analyses), with nearly 100% of sample populations having detectable BPA or BPA metabolites [reviewed in 39].…”
Section: Bisphenol a Exposurementioning
confidence: 99%